2022
DOI: 10.1111/1475-6765.12568
|View full text |Cite
|
Sign up to set email alerts
|

It depends on personal networks: Feelings of stigmatisation among populist radical right party members

Abstract: Stigmatisation has been recognised as a major factor influencing the fortunes of populist radical right (PRR) parties. While scholars have examined it by taking parties as units of analysis, this study focuses on the individual level by asking Which PRR party members are more likely to feel stigmatised? After offering a novel theoretical explanation for feelings of stigmatisation based on the personal networks in which PRR grassroots members are embedded, it then investigates stigma using an original membershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In so doing, they suggest that the relation between norms and elite behavior is complex, and that both can affect one another. This conclusion supports the work of Ammassari (2022) and Art (2011), who have argued that social norms can also affect the behavior and decisions of individuals actively involved in politics.…”
Section: Introductionsupporting
confidence: 88%
“…In so doing, they suggest that the relation between norms and elite behavior is complex, and that both can affect one another. This conclusion supports the work of Ammassari (2022) and Art (2011), who have argued that social norms can also affect the behavior and decisions of individuals actively involved in politics.…”
Section: Introductionsupporting
confidence: 88%
“…The radical right is a party family with similar characteristics in different countries (Mudde 2007;Norris 2005;Rydgren 2005), as are the policiy positions that make these parties counternormative. Moreover, previous literature has assumed an overall stigma against this party family, regardless of their specific country (Ammassari 2022;Bischof and Wagner 2019;Harteveld et al 2019). This suggests that enforcement mechanisms of these norms are likely to travel to other advanced industrial democracies.…”
Section: Discussionmentioning
confidence: 98%
“…Our paper speaks to three main strands of literature in political science and social sciences. First, our results speak to a growing literature on how democracies develop social norms against political behaviours that are regarded as undesirable (Ammassari 2022;Blinder, Ford, and 1 As discussed below, we do not focus on the mainstream Popular Party (PP) as a baseline because previous research has shown that, given its authoritarian connection, this party is counternormative. For example, Valentim (2022) shows that the party is typically under-reported in post-electoral surveys, that Spanish citizens like it less than other parties, and that they place it more to the right than do the experts.…”
mentioning
confidence: 88%
See 1 more Smart Citation